Antibody response to hepatitis B re-vaccination in HIV-infected children with immune recovery on highly active antiretroviral therapy - Lao-araya M. (2014)
Despite a history of hepatitis B virus (HBV) vaccination prior to highly active antiretroviral therapy (HAART), most of HIV-infected children do not have protective antibody to HBV infection. The efficacy of an additional booster dose in children with immune recovery on HAART remains unknown. This study was conducted to determine the response rate of HBV antibody after re-vaccination in HIV-infected children with immune recovery on HAART. Sixty-three successfully HAART-treated HIV-infected children with history of prior HBV vaccination received 10 μg doses of recombinant HBV vaccine (Government Pharmaceutical Organization-Merieux Biological Product, Bangkok, Thailand) intramuscularly at 0, 2 and 6 months. The vaccine response rates were 17.4, 82.5, and 92.1% at 2, 6 and 7 months after the first dose of vaccine, respectively. Plasma HIV RNA level below the limit of detection at the time of re-vaccination was associated with successful vaccine response. HIV-infected children with immune recovery after HAART are likely to benefit from three-dose HBV re-vaccination. © 2007 Elsevier Ltd. All rights reserved.